Electro-optically spectrum switchable, multiwavelength optical parametric oscillators based on aperiodically poled lithium niobate - Wang, Tai-Jie; Deng, Lin-Ming; Chung, Hung-Pin; Chang, Wei-Kun; Pham, Tien-Dat; Tseng, Quan-Hsiang; Geiss, Reinhard; Pertsch, Thomas; Chen, Yen-Hung (Optics Letters, 2020)
We report the first fast switchable multiwavelength optical parametric oscillator based on aperiodic optical superlattice technology. The constructed aperiodically poled lithium niobate (APPLN) integrates the functionalities of two quasi-phase-matching devices on a chip to work simultaneously as an electro-optic (EO) switchable notch-like filter and a multiline optical parametric downconverter. When such an APPLN is built in a 1064-nm-pumped optical resonator system, we achieve the oscillation of dual signals at 1540 and 1550 nm, for a single signal at 1540 nm, and a single signal at 1550 nm in the system when the 3-cm-long APPLN is driven by 0 V, 354 V, and 805 V, respectively. The switching among the three signal spectra is operationally simple and electro-optically fast. The electro-optically switched signals also feature enhanced power spectral density due to the unique EO gain-spectrum filtering mechanism employed in this work.
CRIS-Team Scopus Importer:2023-04-20